Pericardial Tamponade in a Patient with Inactive Ulcerative Colitis. (10th February 2010) - Rezaie, Ali; Wong, Karen; Gyenes, Gabor
Abstract : Cardiac tamponade is a rare extraintestinal manifestation of ulcerative colitis. We present a case report of tamponade occurring four years after curative proctocolectomy and in the absence of any medical therapy for ulcerative colitis. Options for medical management of this condition are also discussed.